Nekatere skladenjske posebnosti v delih Ivana Cankarja - Smolej, Mojca (Jezik in slovstvo, 2018)
The textual form of the works of Ivan Cankar not only has an aesthetic role but above all serves as a building block of his textual world. The syntactic rhythm reveals the content and, conversely, the content conditions the syntactic form. A variety of syntagms, phrases, word order, and renovations at almost all linguistic levels together form the meaning. The present article sets out to highlight some of Cankar's more prominent syntactic building blocks of textual world, or stylistic devices.
Keywords: Cankar, Ivan; jezikovna stilistika; skladnja; slovenščina; stavek; stilem